KONFLIK ROHINGYA: AKAR MASALAH, PENYELESAIN, DAN PERAN INDONESIA - Mahfud Khoirul Amin (The Indonesian Islamic Studies and International Relations Association (Insiera), 2018)
The prolonged conflict in Rohingnya has resulted in many victims. This humanitarian crisis attracted the attention of a globalized world. International organizations and several countries are flocking to solve this problem. However, some constraints and problems in completing it. Therefore this article will attempt to explain the cause of conflict and some of the world's global efforts in completing it. In this paper will also discussed some of the problems and also Indonesia's role in resolving this conflict. As well as some of the criticism and suggestions to solf the conflict in rohingnya.